The growth and evolution of DDoS. (October 2015) - Mansfield-Devine, Steve
Abstract : Distributed Denial of Service (DDoS) attacks show no signs of going away. In fact, they are finding popularity with new groups of users and moving away from the low-grade extortion carried out by small groups of cyber-criminals to being deployed as political weapons and even, it would appear, by individuals bearing grudges. And when they are exploited for the original purpose – of blackmail – DDoS attacks are becoming more complex and sophisticated.